Lectures in Commercial Law - Dr. LABIDI Lazhar (جامعة الوادي University of El Oued, 2024)
Our decision to teach the subject of Commercial Law to the students of the Faculty of Law at the University of Martyr Hamma Lakhdar in El Oued, Algeria, was the direct motivation behind the idea of preparing this book. It is intended to be a helpful resource for students studying the first part of Commercial Law, which includes five chapters: an overview of Commercial Law, the aspects of its independence from Civil Law, the special provisions governing commercial transactions, the trader, and the commercial establishment.
Pedagogical Publication Presented to Second-Year Law Students (LMD)